Identifikasi Cemaran Mikroba Pada Daging Sapi di Pasar Tradisional Kabupaten Serdang Bedagai - Mhd Teguh Dwi Pradana; Nur Asmaq; Purwo Siswoyo (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Beef is a highly nutritious food source and is essential for fulfilling human nutritional needs. Good-quality meat can be obtained in traditional markets with hygienic conditions and minimal microbial contamination. Inadequate sanitation can trigger various diseases; therefore, proper sanitation practices in traditional markets are crucial as preventive and monitoring measures to prevent the spread of infectious diseases in the community. Serdang Bedagai Regency is one of the regencies in North Sumatra whose main source of animal protein comes from beef. There are several traditional markets in this regency, such as Sei Rampah Public Market, Bedagai Market, and Bengkel Market. These three locations are the centers of beef sales in Serdang Bedagai Regency. This study aims to analyze microbial contamination in beef sold in several traditional markets in Serdang Bedagai Regency. The study used a descriptive method to determine bacterial contamination in beef. Research parameters included observation of Total Plate Count (TPC) and microbial contamination analysis, including E. coli, Staphylococcus aureus, and Salmonella spp. contamination. The results showed the highest TPC at SR3 with 2 × 10⁷ CFU/g, the highest E. coli contamination at TB2 with 78 × 10³ CFU/g, the highest Staphylococcus aureus contamination at SR3 with 378 × 10² CFU/g, and only the SR3 sample was positive for Salmonella spp. contamination. Based on the Indonesian National Standard (SNI) No. 7388-2009 on the maximum limit of microbial contamination in food, the test results for TPC, E. coli, and Staphylococcus aureus contamination exceeded the threshold, and one sample was found to contain Salmonella spp.